Online courses in the educational process of a university - S. A. Bibalova; A. V. Leontyeva (Вестник Майкопского государственного технологического университета)
Currently, e-learning content has become firmly established in the practical activities of university teachers. A lot of research is devoted to substantiating the possibilities of distance learning as a new format of education in the era of the digital revolution. The research problem is increasing the effectiveness of using online courses in the educational process of a university. The purpose of the research is to substantiate the possibilities of using online courses in the educational practice of universities as relevant content of a digital service. To achieve this goal, theoretical research methods were used (analysis, synthesis, differentiation, generalization, description), as well as methods of visual representation. The research results: the authors of the article have clarified the concept of «online course», determined the relationship between the categories «e-learning», «distance learning», «online learning», and considered a model of the structure of the online course; the advantages of using online courses for universities have been presented; The negative and positive aspects of the use of online courses by teachers in the educational process have been identified, and taking into account the analysis of experience accumulated in teaching practice, the most optimal options for using online courses at a university have been presented. Key conclusions: an online course is understood as e-learning content, which is an educational and methodological resource for conducting educational activities in the discipline; the optimal use of online courses in a mixed format (in combination with traditional classroom work). The orientation of universities towards the use of online courses in educational practice corresponds to current global trends in education.